Strong intrinsic room-temperature ferromagnetism in freestanding non-van der Waals ultrathin 2D crystals - Wu, Hao; Zhang, Wenfeng; Yang, Li; Wang, Jun; Li, Jie; Li, Luying; Gao, Yihua; Zhang, Liang; Du, Juan; Shu, Haibo; Chang, Haixin (Nature communications, 2021)
Control of ferromagnetism is of critical importance for a variety of proposed spintronic and topological quantum technologies. Inducing long-range ferromagnetic order in ultrathin 2D crystals will provide more functional possibility to combine their unique electronic, optical and mechanical properties to develop new multifunctional coupled applications. Recently discovered intrinsic 2D ferromagnetic crystals such as Cr 2 Ge 2 Te 6 , CrI 3 and Fe 3 GeTe 2 are intrinsically ferromagnetic only below room temperature, mostly far below room temperature (Curie temperature, ~20–207 K). Here we develop a scalable method to prepare freestanding non-van der Waals ultrathin 2D crystals down to mono- and few unit cells (UC) and report unexpected strong, intrinsic, ambient-air-robust, room-temperature ferromagnetism with T C up to ~367 K in freestanding non-van der Waals 2D CrTe crystals. Freestanding 2D CrTe crystals show comparable or better ferromagnetic properties to widely-used Fe, Co, Ni and BaFe 12 O 19 , promising as new platforms for room-temperature intrinsically-ferromagnetic 2D crystals and integrated 2D devices. Van der Waals crystals have recently been shown to exhibit ferromagnetism, however the Curie temperature is typically quite low. Herein, Wu et al succeed in producing mono and few layer crystals of CrTe, a non-van der Waals crystal, and demonstrate strong intrinsic room temperature ferromagnetism.